During Hospitalization, Older Patients at Risk for Malnutrition Consume <0.65 Grams of Protein per Kilogram Body Weight per Day. (24th June 2020) - Weijzen, Michelle E. G.; Kouw, Imre W. K.; Geerlings, Phil; Verdijk, Lex B.; van Loon, Luc J. C.
Abstract: Background: Malnutrition is prevalent in hospitalized patients. To support muscle maintenance in older and chronically ill patients, a protein intake of 1.2–1.5 g/kg/d has been recommended during hospitalization. We assessed daily protein intake levels and distribution in older patients at risk for malnutrition during hospitalization. Methods: In this prospective, observational study, we measured actual food and food supplement consumption in patients ( n = 102; age, 68 ± 14 years; hospital stay, 14 [8–28] days) at risk of malnutrition during hospitalization. Food provided by hospital meals, ONS, and snacks and the actual amount of food (not) consumed were weighed and recorded for all patients. Results: Hospital meals provided 1.03 [0.77–1.26] protein, whereas actual protein consumption was only 0.65 [0.37–0.93] g/kg/d. Protein intake at breakfast, lunch, and dinner was 10 [6–15], 9 [5–14], and 13 [9–18] g, respectively. The use of ONS ( n = 62) resulted in greater energy (1.26 [0.40–1.79] MJ/d, 300 [100–430] kcal/d) and protein intake levels (11 [4–16] g/d), without changing the macronutrient composition of the diet. Conclusion: Despite protein provision of ∼1.0 g/kg/d, protein intake remains well below these values (∼0.65 g/kg/d), as 30%–40% of the provided food and supplements is not consumed. Provision of ONS may increase energy and protein intake but does not change the macronutrient composition of the diet. Current nutrition strategies to achieve the recommended daily protein intake in older patients during their hospitalization are not as effective as generally assumed.